2016
DOI: 10.1590/s1678-9946201658029
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Leishmaniasis in Petrolina, State of Pernambuco, Brazil, 2007-2013

Abstract: SUMMARYVisceral leishmaniasis is a life-threatening disease of great public health relevance in Brazil. The municipality of Petrolina is an endemic area in the State of Pernambuco, Brazil. This study was designed to assess the recent expansion of VL in the municipality of Petrolina, Pernambuco. Patients data were obtained from the Brazilian National Information System for Notifiable Diseases (SINAN). A total of 111 records from 2007 to 2013 were investigated, of which 69 were residents in Petrolina. The diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
4
6
0
6
Order By: Relevance
“…Regarding sex, it is expected that there was no difference in the incidence of HVL in people up to 19 years of age, or that there was a small predominance in men, and at 20 years of age or over, a predominance in men 33 . However, in Araçatuba, there was a higher incidence in female patients aged 0-4 years, a result coincident with that obtained in Birigui 12 and in a study conducted in Petrolina, Pernambuco State, Brazil 34 . With regard to the incidence of HVL in patients aged 20 years and over, Botelho and Natal 33 found that in the City of Campo Grande, MS, the risk of developing HVL was higher in men, which similar to that observed in Araçatuba.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding sex, it is expected that there was no difference in the incidence of HVL in people up to 19 years of age, or that there was a small predominance in men, and at 20 years of age or over, a predominance in men 33 . However, in Araçatuba, there was a higher incidence in female patients aged 0-4 years, a result coincident with that obtained in Birigui 12 and in a study conducted in Petrolina, Pernambuco State, Brazil 34 . With regard to the incidence of HVL in patients aged 20 years and over, Botelho and Natal 33 found that in the City of Campo Grande, MS, the risk of developing HVL was higher in men, which similar to that observed in Araçatuba.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, we confirmed that this region continues to account for more than half of all HVL cases in the country, and Pernambuco is among the 10 states with the greatest number of cases. Regarding HVL occurrence in Pernambuco State, there is a higher incidence of HVL in the Agreste and Sertão regions, as previously described by several authors 15,16,[22][23][24] .…”
Section: Discussionsupporting
confidence: 65%
“…We further observed that the incidence of VL was twice as high in males than in females in both municipalities and was higher among people younger than 15 years and residents of rural areas. These data are similar to those reported by Araújo et al 9 , who analyzed data from Petrolina between 2007 and 2013 9 . The increased susceptibility among those younger than 15 years can be explained by immunological immaturity 15,16 , which is aggravated by the malnutrition usually present in endemic areas and by increased exposure to the vector in peri-domestic areas 6 .…”
Section: Discussionsupporting
confidence: 91%
“…Both municipalities are classified as intense areas of VL transmission, as both maintained an annual average of >4.4 cases during the past 5 years 6 . During the studied period, the municipality of Petrolina had an average of 14 cases per year, greater than the number reported by Araújo et al 9 in this municipality between 2007 and 2013 9 .…”
Section: Discussionmentioning
confidence: 53%